The dependence of anti-corrosion behaviors of iron sulfide films on different reactants. (10th July 2020) - Xie, Chuang; Wang, Boyi; Li, Shujie; Wen, Xiangli; Wei, Shikai; Zhang, Shuai; Feng, Min; Chen, Liqiang; Zheng, Shuqi
Abstract: As the product of hydrogen sulfide corrosion, iron sulfide compound can be used as hydrogen permeation barrier. In this study, chemical vapor deposition was used to synthesize iron sulfide films on the surface of X80 steel with different sulfur sources, and the effects of different sulfur sources on the products were studied. The film was characterized by its morphology, composition and performance. The results show that the hydrogen resistance of our product and the bonding degree between the substrate and the film are strongly relevant with the compactness of the films. When we used TBDS as sulfur source, the highest impendance and the smallest hydrogen permeation current (0.53 μA/cm 2 ) was obtained, which is due to the better adhesion and dense structure compare to the other two sulfur sourses. Highlights: We synthesized the iron sulfide films by CVD method with different sulfur sources. Hydrogen resistance is related to the binding degree and morphology of the films. Nanoindentation results show that the film adhesion is best when the sulfur source is TBDS. The smallest hydrogen permeation current (0.53 μA/cm 2 ) is obtained, only 2.5% of matirx.